Mount Pinatubo Tourist Complex the gateway to the crater - Dionco,Lovely Joanna B. (College of Architecture, University of the Philippines Diliman, 2014)
Tourism at present is one of the fastest and highest growing industries throughout the world. Several numbers of developing countries today are mindful of the economic potential advantage of tourism. Tourism is a key element of the Philippine economy. It is a service-intensive industry focusing on the visitor’s service experiences not only during their stay, but also preceding and subsequent to it. The project was visualized upon learning of the existence of a number of unpredicted visitors, local and foreign tourists, to the locality who travels the area on their way to the crater of Mt. Pinatubo. The Mount Pinatubo Tourist Complex will be specific attraction or place of interest in the community. The complex will provide the essential needs of the tourists of the Mt. Pinatubo and its immediate local travel destinations. Through this tangible project, it will allow to gain more profit to assist in the economic status of the locality and attract more tourists to visit Mt. Pinatubo and other immediate local tourist spots. This project will promote economic and tourism development opportunities, benefits for the local community and potential investors within and outside the area. One of its main objectives is to provide better quality lives for the local community thru travel and tourism. It dynamically encourage eco-tourism travel, highlighting cultural experience within the area and physical interactions among the locals.